Քաջարան քաղաքում ապրող աշխատունակ կանանց փաստացի սննդում մակրո և միկրոսննդանյութերի պարունակության ուսումնասիրության արդյունքները և դրանց հիգիենիկ գնահատականը - Մ. Ա. Մկրտչյան; Վ. Յու. Կոգան; Մ. Ս. Բարխուդարյան; Ռ. Դ. Հովհաննեսյան; Գ. Պ. Մուրադյան; Ա. Գ. Մարգարյան; Ա. Գ. Գևորգյան (Հայաստանի ԳԱԱ)
Изучена обеспеченность основными пищевыми веществами и микронутриентами 84 образцов суточных рационов питания женщин II профессиональной группы, проживающих в городе Каджаране. В пищевых суточных рационах выявлен дефицит полноценных белков животного происхождения и эссенциальных жирных кислот.It was studied the availability by basic nutrients and micronutrients of 84 samples of daily rations of women’s II professional groups, residing in the town of Kajaran. In their daily rations it has been revealed a deficit of proteins of animal origin and essential fatty acids. The principal danger contained the insufficient content of folic acid and vitamin B12 (58,3 and 97,2%) in the daily rations of women. The daily deficit in folic acid ranged from 39 to 40%. Only 33% of daily rations contained sufficient quantities of calcium and 50 % of the studied women received the necessary quantity of folium.
Keywords: Medicine; Public aspects of medicine